Analytical assessment and comparison of facilities management services for residential estates - H. K. Lai, Joseph (International Journal of Strategic Property Management, 2012)
Populous places are particularly in need of high-rise residential buildings, which are increasingly built as estates. The facilities in these estates entail proper management in order to serve the numerous residents there. Aimed at evaluating the facilities management (FM) services for three major kinds of residential estates (‘public’, ‘semi-public’ and ‘private’), a study was conducted based on a performance-importance-cost (PIC) evaluation model. The end-users’ perceived importance and performance levels and the cost data of the FM services for a public estate, a semi-public estate and a private estate were analyzed using the analytical hierarchy process (AHP), analysis of variance (ANOVA) and Fisher’s least significant difference (LSD) procedure. The importance and performance levels of the services and their differences between the estates were revealed. The highest service performance and cost levels were found with the private estate, followed by the semi-public estate and the public estate, while the orders of their cost-effectiveness reversed. Rather than assessing merely the cost or performance of services, using the approach of this study to examine their cost-effectiveness can enable more holistic evaluations towards strategic property management. First Publish Online: 2 Oct 2012